Real Options Effects on Employment : Does Exchange Rate Uncertainty Matter for Aggregation? - Matthias Göcke; Ansgar Belke (Institute for the Study of Labor (IZA), 2004)
In a baseline micro model a band of inaction due to hiring- and firing-costs is widened by option value effects of exchange rate uncertainty. Based on this micro foundation an aggregation approach is presented. Under uncertainty, intervals of weak response to exchange rate reversals (called 'play' areas) are introduced on the macro-level. 'Spurts' in new employment or firing may occur after an initially weak response. Since these mechanisms may apply to other "investment" cases where the aggregation of microeconomic real options effects under uncertainty are relevant, they may even be of a more general interest.
Keywords: D81; F41; J23; 330; aggregation; employment hysteresis; exchange rate uncertainty; real options; Arbeitsnachfrage; Wechselkursrisiko; Aggregation; Beschäftigung; Hysteresis; Realoption; Theorie